Libya's conflicts enter a dangerous new phase - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2019)
Recent advances by Khalifa Haftar's 'Libyan Arab Armed Forces' in southern Libya are changing power relations in Libya in ways that undermine the UN's ongoing attempts at brokering a political solution. Haftar's increasing influence implies he will be less open to concessions, while key forces in western Libya now perceive him as an existential threat. The Tripoli-based Government of National Accord (GNA), which has, to date, remained ambivalent towards Haftar despite his open opposition towards it, will come under increasing pressure from both adversaries and allies of Haftar to clarify its stance. The new configuration raises the risk of escalation on multiple fronts. Only the emergence of a stable balance of power can create the conditions for a political settlement
Keywords: 320